2019
DOI: 10.1002/sdtp.12957
|View full text |Cite
|
Sign up to set email alerts
|

33‐3: TADF Emitter Selection for Deep‐Blue Hyper‐Fluorescent OLEDs

Abstract: Blue fluorescent OLEDs are still the bottleneck for the power consumption in today´s OLED panels. In recent years, the TADF technology has shown fast progress towards high-efficiency deepblue emitter systems. The TADF technology can be used in a selfemitting or in a co-emitting (or hyper) approach. To make the coemitting system work efficiently, the combination of TADF and fluorescent emitter has to be chosen carefully. In this paper, we will discuss how to match TADF and fluorescent emitter combinations for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In this approach, TADF sensitizers and fluorescent emitters are embedded as dopants in a host matrix, so that Förster resonance energy transfer (FRET) can occur from the S 1 TADF state of a TADF molecule to the S 1 FE state of a fluorescent emitter. Because of the high radiative decay rates and narrow emission spectra of the latter, fast and complete FRET increases not only the OLED stability but also its color purity. …”
mentioning
confidence: 99%
“…In this approach, TADF sensitizers and fluorescent emitters are embedded as dopants in a host matrix, so that Förster resonance energy transfer (FRET) can occur from the S 1 TADF state of a TADF molecule to the S 1 FE state of a fluorescent emitter. Because of the high radiative decay rates and narrow emission spectra of the latter, fast and complete FRET increases not only the OLED stability but also its color purity. …”
mentioning
confidence: 99%
“…We have previously shown that by choosing a matched combination of TADF emitter and a fluorescent acceptor, very high Förster radii even in deep-blue can be achieved. [7] For example, the system shown in Figure 3 using a CYNORA TADF emitter has a Förster radius of 3.6 nm and a blue hyperfluorescence emission with CIEy = 0.17.…”
Section: -3 / T Baumannmentioning
confidence: 99%
“…OLED displays have some interesting features that endow them with amazing features over other established technologies, such as LCDs. [1][2][3][4] As compared to LCDs, OLEDs do not possess a backlight system. However, they possess some interesting features such as enhanced resolution, high contrast ratio, transparent displays, wider viewing angles, and faster response time.…”
Section: Introductionmentioning
confidence: 99%
“…However, they possess some interesting features such as enhanced resolution, high contrast ratio, transparent displays, wider viewing angles, and faster response time. [1][2][3][4] The most important feature is the flexibility of these displays, which can be twisted and rolled up similar to a poster, opening new doors to the practical applications of these displays. However, OLEDs still have some issues with regards to their material development and device architecture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation